Ammonia decomposition over SiO2-supported Ni–Co bimetallic catalyst for COx-free hydrogen generation. (29th May 2020) - Wu, Ze-Wei; Li, Xin; Qin, Yuan-Hang; Deng, Lidan; Wang, Cun-Wen; Jiang, Xingmao
Abstract: NH3 decomposition over non-noble catalyst to generate COx -free H2 has attracted great attention in recent years. In this work, fumed SiO2 -supported Ni, Co and Ni–Co bimetallic catalysts are synthesized by using a co-impregnation method and evaluated for NH3 decomposition, which shows that the bimetallic catalysts exhibit better catalytic activity than the monometallic ones. This enhanced activity observed on bimetallic catalyst can be largely attributed to the more appropriate catalyst metal-N binding energy resulting from the synergistic effect between Ni and Co in the formed Ni–Co alloy. Among the synthesized catalysts, Ni5 Co5 /SiO2 synthesized with the Ni/Co molar ratio of 5:5 achieves 76.8% NH3 conversion under a GHSV of 30, 000 mL h −1 g −1 cat at 550 °C and shows the best catalytic activity, which can be further improved by doping with K (78.1% NH3 conversion at 30, 000 mL h −1 g −1 cat ), and the obtained Ni5 Co5 /SiO2 –K also shows excellent catalytic stability. Highlights: Proper M − N binding energy is observed on Ni–Co catalyst for NH3 decomposition. Ni–Co catalysts show better NH3 decomposition activity than the monometallic ones. Ni5 Co5 /SiO2 has 76.8% NH3 conversion under a GHSV of 30, 000 mL h −1 g −1 cat at 550 °C. Ni–Co catalyst doped with K has better catalytic performance for NH3 decomposition.